Museum in the Classroom and Classes in the Museum — How to Integrate Museum Education into the Polish as a Foreign Language Teaching - Žák-Caplot, Katarzyna (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
The aim of the article is to indicate possible ways of using elements of contemporary museum education during Polish as a foreign language classes in the classroom and outside it (in this case in the space of a cultural institution) as well as to draw attention to learners’ needs and good practices in constructing templates for language classes in a museum. The text also presents examples of the implementation of language programmes in Polish and foreign museums, focusing on their strengths and weaknesses. Selected topics are discussed from the perspective of language and museum educators.